1997
DOI: 10.1037/0278-7393.23.4.968
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolation: The sine qua non for abstraction in function learning.

Abstract: ion was investigated by examining extrapolation behavior in a function-learning task. During training, participants associated stimulus and response magnitudes (in the form of horizontal bar lengths) that covaried according to a linear, exponential, or quadratic function. After training, novel stimulus magnitudes were presented as tests of extrapolation and interpolation. Participants extrapolated well beyond the range of learned responses, and their responses captured the general shape of the assigned functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
380
3
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 165 publications
(410 citation statements)
references
References 29 publications
24
380
3
3
Order By: Relevance
“…The performance for the test items outside the trained range (transfer) helps to inform us on this issue. Formal exemplar models indicate that if the subject learns only the inputoutput points during training and then applies only the individually learned exemplars to support responses on transfer points (outside the trained range), performance along the transfer region is fairly flat; that is, there is no extrapolation of the slope inscribed by the training points (see DeLosh et al, 1997, for modeling and examples of individuals displaying this pattern of extrapolation). Accordingly, if test/study training promotes only learning of individual training points and these points are used individually to generate transfer responses, then the advantage observed for that training procedure for trained points would be eliminated (or dramatically reduced) on the transfer points (outside the trained range).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The performance for the test items outside the trained range (transfer) helps to inform us on this issue. Formal exemplar models indicate that if the subject learns only the inputoutput points during training and then applies only the individually learned exemplars to support responses on transfer points (outside the trained range), performance along the transfer region is fairly flat; that is, there is no extrapolation of the slope inscribed by the training points (see DeLosh et al, 1997, for modeling and examples of individuals displaying this pattern of extrapolation). Accordingly, if test/study training promotes only learning of individual training points and these points are used individually to generate transfer responses, then the advantage observed for that training procedure for trained points would be eliminated (or dramatically reduced) on the transfer points (outside the trained range).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, if test/study training promotes only learning of individual training points and these points are used individually to generate transfer responses, then the advantage observed for that training procedure for trained points would be eliminated (or dramatically reduced) on the transfer points (outside the trained range). Furthermore, the slopes of the outputs in the transfer region would be flat (see DeLosh et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 For example, DeLosh et al (1997) tested the ability of an eliminative connectionist model to extrapolate linear, exponential, and quadratic functions, and compared that result with the extrapolation abilities of human subjects. They found that although humans were able to extrapolate these functions beyond the range of trained responses, the eliminative connectionist model that they studied was not able to extrapolate adequately beyond the range of trained responses.…”
Section: Evidence From Simulationsmentioning
confidence: 99%